FOXM1-Mediated LINC-ROR Regulates the Proliferation and Sensitivity to Sorafenib in Hepatocellular Carcinoma - Yingru Zhi; Mubalake Abudoureyimu; Hao Zhou; Ting Wang; Bing Feng; Rui Wang; Xiaoyuan Chu (Elsevier, 2019)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-associated death worldwide. Indeed, despite the benefit of sorafenib in the treatment of some patients with HCC, the majority of these patients have a poor response to or intolerance of sorafenib, resulting in further tumor progression. Exploring the mechanisms underlying sorafenib resistance is essential to the treatment of HCC. Long noncoding RNAs (lncRNAs) are known as participants in tumorigenesis. In this study, we identified that long intergenic non-protein coding RNA, regulator of reprogramming (LINC-ROR), was upregulated in HCC cell lines, which was transcriptionally activated by FOXM1. Furthermore, the sponging of miR-876-5p by LINC-ROR released FOXM1, thereby forming a positive-feedback loop. Additionally, we demonstrated that upregulation of both FOXM1 and LINC-ROR impaired the sensitivity to sorafenib in HCC cells. The role of this feedback loop was demonstrated by rescue assays. These results revealed a novel molecular feedback loop between LINC-ROR and FOXM1 and elucidated their functions in sorafenib sensitivity of HCC cell lines. Keywords: LINC-ROR, FOXM1, miR-876-5p, HCC, sorafenib, sensitivity